THE USE OF SOUND BOOK TO ENHANCE STUDENTS' ARABIC VOCABULARY MASTERY - Mardhatillah, Mardhatillah; Muhtadi, Ali (Universitas Labuhanbatu, 2025)
Purpose – The limited use of learning media by teachers, which leads to a primarily one-way learning process, is the main reason for this study. Student learning outcomes are adversely affected by this lack of interaction in the classroom, particularly in Arabic language studies. The study intends to (1) figure out whether students who are taught using the sound book 'أول كتاب and those who do not have a notable difference in their mastery of Arabic vocabulary and (2) assess how well the sound book 'أول كتاب enhance students' Arabic vocabulary mastery.Methodology – This study employs a quantitative approach with an experimental research design, specifically a pretest-posttest control group design. The population consists of three classes, comprising a total of 105 students. The sample, selected using a simple random sampling technique, consists of two classes: Class I-A, the experimental group, and Class I-B, the control group. Data collection methods include tests, interviews, and documentation. For data analysis, a t-test was used to examine differences in students' mastery of Arabic vocabulary, while the N-gain test was applied to determine the level of effectiveness.Findings – The results of the t-test on the post-test scores for the experimental and control classes indicate a Sig. (2-tailed) value of 0.001, demonstrating a significant difference in Arabic vocabulary mastery between students in the experimental class, who were taught using the sound book 'أول كتاب, and those in the control class, who were taught without it. Furthermore, the N-gain test for the experimental class yielded a percentage of 75%, indicating an effective enough level. Based on these findings, it can be concluded that the use of the sound book 'أول كتاب is effective enough in enhancing students' mastery of Arabic vocabulary.Contribution – These findings have implications for the use of sound books as a valuable resource for teachers in selecting appropriate learning media to create a more effective and interactive learning experience. This demonstrates the potential of sound books to enhance students' engagement and understanding through their interactive and multi-sensory features